MODAL SOSIAL DALAM PEMBANGUNAN HUTAN (PENYELESAIAN DEFORESTASI DAN KONFLIK PHBM) - , RAHMANTA SETIAHADI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research purposes to find an explanation how the role of social capital in development of forests for settlement of deforestation and forest resource management conflicts involving the community through CBFM. Another purpose of this study was seeking clarification community relations role of social capital in addressing deforestation forest, looking for explanations of social capital in the form of material activity and the implementation of the principles of CBFM, seeking an explanation of social capital utilization in CBFM implementation of conflict management, as well as finding an explanation elaboration capital and social forestry development. Research conducted in the Ngawi District covers an area of three KPH Ngawi, KPH Lawu Ds, and KPH Saradan. This study used qualitative analysis to analyze or explain the social capital in forestry development with a focus to understand social action in forest management with communities (CBFM) with descriptive method. Data were collected through in-depth interviews with resource persons who are considered to have in-depth information about deforestation, CBFM and conflict as well as field observations. The data analysis starts with organizing all the data, with information gathering step, through interviews, questionnaires and direct observation